Rights and duties of the Unified Health System users: experience report - Castro, Bruna Carolina Sousa (2019)
This article aims to report the experience of the group Programa de Educação Tutorial (Program of Tutorial Education) regarding the university extension project "Rights and Duties of the SUS users". Said project took place from October to December 2016, in the general surgery and orthopedics wards of a teaching hospital. Ten students and six professors of the nursing graduation course participated. The study used the knowledge developed from a dialogic perspective in the approach of the Charter of Health Users Rigths. The project aimed at contributing to empower the patients regarding their rights and duties as SUS users, so that they have autonomy to demand for them. When rights and duties of SUS users are articulated and strong in the health services, this can lead to an increased quality, equity, and a greater capacity to deal with problems, generating a more dignified, just, and equal assistance.